A History of Europe : Volume 1 from the earliest times to 1713 - H.A.L Fisher (Great Britain HAL Fisher, 1935)
Single volume history of Europe from the Ancient Greeks to the 1930's
Keywords: History of Countries -- History of Countries; History of Europe -- History of Europe